Analisis Efektivitas Dan Kontribusi Dari Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan (PBB-P2) Terhadap Pendapatan Asli (PAD) - Alifiya Sandyah Putri; Priyo Hari Adi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The authority of local governments in regulating PBB-P2 is regulated in Law Number 28 of 2009 concerning regional taxes and regional levies. The government requires by 2014 that all districts and cities in Indonesia carry out their obligations to regulate PBB-P2. The transfer of PBB-P2 from central tax to regional tax is to increase regional autonomy. Due to the transfer, it directly adds to the revenue sector for PAD. PAD is one of the supporting sectors for regional spending, therefore between PBB-P2, PAD, and regional expenditures are interrelated. This study uses 35 districts and cities in Central Java in the period 2014 – 2018. The purpose of this study was to determine the effectiveness and contribution of PBB-P2 to PAD and its effect on regional spending after the transfer to local taxes. This study uses secondary data obtained from the Directorate General of Fiscal Balance and regional reports in figures. Keywords: PBB-P2 Effectiveness, PBB-P2 Contribution, PAD, Regional Expenditures